2013
DOI: 10.2217/pgs.13.166
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Association Study in NSAID-Induced Acute Urticaria/Angioedema in Spanish and Han Chinese Populations

Abstract: The associations described were different from those related to the metabolism of arachidonic acid and could provide new mechanisms underlying NSAID-induced AUA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
31
0
2

Year Published

2014
2014
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(33 citation statements)
references
References 70 publications
0
31
0
2
Order By: Relevance
“…We recently conducted the only GWAS for NIUA using 2 independent populations from Spain and Taiwan [129]. Suggestive associations were found for 3 genetic clusters in the Spanish group (RIMS1, BICC1, and RAD51L1) and 1 region in the Han Chinese group (ABI3BP).…”
Section: Beyond the Candidate Gene Approachmentioning
confidence: 99%
See 1 more Smart Citation
“…We recently conducted the only GWAS for NIUA using 2 independent populations from Spain and Taiwan [129]. Suggestive associations were found for 3 genetic clusters in the Spanish group (RIMS1, BICC1, and RAD51L1) and 1 region in the Han Chinese group (ABI3BP).…”
Section: Beyond the Candidate Gene Approachmentioning
confidence: 99%
“…Suggestive associations were found for 3 genetic clusters in the Spanish group (RIMS1, BICC1, and RAD51L1) and 1 region in the Han Chinese group (ABI3BP). Most of these regions are linked to the Ca2 + , cAMP, and/or P53 signaling pathways [129].…”
Section: Beyond the Candidate Gene Approachmentioning
confidence: 99%
“…Studies that have assessed the genetic variants potentially associated with immediate-type hypersensitivity to NSAIDs were predominantly conducted in Spain (41)(42)(43)(44)(45)(46)(47)(48). They reported an association with genes belonging to HLA genes (HLA-DRB1, HLA-B44, and HLA-Cw5) (43,44) or to the arachidonic acid pathway (ALOX5, ALOX5AP, ALOX15, TBXAS1, PTGDR, and CYSLTR1) (46, 49) ( Table 3).…”
Section: Genetic Predictors Of Nar To Nsaids Including Aspirinmentioning
confidence: 99%
“…A case-control study evaluated the histamine-producing pathway and showed a weak association with the diamine oxidase gene (DAO) (43). Only one study used a GWAS approach and suggested the potential implication of the CEP68 gene (encoding centrosomal protein of 68 KDa) in the development of hypersensitivity reactions to NSAIDs (48).…”
Section: Genetic Predictors Of Nar To Nsaids Including Aspirinmentioning
confidence: 99%
See 1 more Smart Citation